Innovating government normative, policy and technological dimensions of modern government - van der Hof, Simone; Groothuis, Marga M. (Information technology and law series, 2011)
The aim of this book is to analyze four dimensions of innovating government and the use of new technologies: legal, ethical, policy and technological dimensions. By joining authors from a diversity of backgrounds (law, ethics, public administration, political science, sociology, communications science, information science, and computer science) in one book, readers (academics, policy makers, legislators and others) are confronted with a variety of disciplinary perspectives on persistent themes, like privacy, biometrics, surveillance, e-democracy, electronic government, and identity management, that are central to today?s evolution of new modes of modern government.